The Rise of Citizen Science. - Toerpe, Kathleen (Futurist)
The article discusses the public participation in scientific research, or citizen science, which involves the use of crowdsourcing to gather data for scientific research. The author looks at the use of citizen science in the field of ornithology, evidenced by Cornell University's Ornithology Lab. Topics include massive online citizen science projects such as SETILive's Allen Telescope Array, which searched for extraterrestrial life, the use of citizen science in STEM academic disciplines, as well as Yale University's partnership with the computer platform Zooniverse to gather data for its Planet Hunters science project.